Effectiveness of antipsychotic drugs against hostility in patients with schizophrenia in the Clinical Antipsychotic Trials of Intervention Effectiveness (CATIE) study. (28th November 2013) - Volavka, Jan; Czobor, Pál; Citrome, Leslie; Van Dorn, Richard A.
<x content-type="archive" xml:space="preserve">Abstract</x> Introduction Aggressive behavior can be a dangerous complication of schizophrenia. Hostility is related to aggression. This study aimed to compare the effects of olanzapine, perphenazine, risperidone, quetiapine, and ziprasidone on hostility in schizophrenia. Methods We used the data that were acquired in the 18-month Phase 1 of the Clinical Antipsychotic Trials of Intervention Effectiveness (CATIE) study. We analyzed the scores of the Positive and Negative Syndrome Scale (PANSS) hostility item in a subset of 614 patients who showed at least minimal hostility (a score ≥ 2) at baseline. Results The primary analysis of hostility indicated an effect of difference between treatments (F4, 1487 = 7.78, P < 0.0001). Olanzapine was significantly superior to perphenazine and quetiapine at months 1, 3, 6, and 9. It was also significantly superior to ziprasidone at months 1, 3, and 6, and to risperidone at months 3 and 6. Discussion Our results are consistent with those of a similar post-hoc analysis of hostility in first-episode subjects with schizophrenia enrolled in the European First-Episode Schizophrenia Trial (EUFEST) trial, where olanzapine demonstrated advantages compared with haloperidol, quetiapine, and amisulpride. Conclusion Olanzapine demonstrated advantages in terms of a specific antihostility effect over the other antipsychotics tested in Phase 1 of the CATIE trial.